Integrating structured individual offending pathway analysis into group treatment for individuals who have accessed, shared, and/or distributed child sexual exploitation material: a feasibility study and preliminary outcome evaluation. Issue 6 (3rd July 2021) - Merdian, Hannah L.; Perkins, Derek; McCashin, Darragh; Stevanovic, Jelena
ABSTRACT: The Child Sexual Exploitation Material Pathways Tool (CPT) is a case formulation tool that guides a systematic exploration of the learning history, current personal situation, and offending behaviour of individuals who have been arrested, cautioned, and/or sentenced for accessing, downloading, distributing, and/or sharing of child sexual exploitation material. Based on the RE-AIM principles, a feasibility study was conducted to test the integration of the CPT as part of a community treatment group in comparison to treatment-as-usual. Based on qualitative feedback from the participants and group facilitators, the study evidenced that participants (and service staff) can be successfully recruited for this intervention, that the intervention has perceived positive effects, and that it can be integrated into treatment-as-usual. The study also highlighted critical issues in the quantitative evaluation of feasibility studies in a forensic context and with regards to the CPT specifically. Limitations of the study are the small sample size and the number of drop-outs over time. Findings are discussed with regards to planned revisions to the CPT and research developments towards a randomised controlled trial.